Analysis of the Implementation of Educators and Educational Staff at Pamijahan Elementary School - Heni H; Teni Hardiyani; Tesa Esti Rahayu (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose this research is related to the assessment of the quality of educators and educational personnel. This research is descriptive research with a qualitative approach. The data collection technique for this research is a closed questionnaire and documentation. The purpose of this study is to measure the suitability of the National Education Standard Quality Indicators (SNP) with the facts on the ground, as well as to find out the strengths, weaknesses, opportunities, and threats in an educational unit. The research subjects were educators and education staff of SDN Pamijahan. The study also explores the data with SWOT analysis. The results showed that the quality of educators was in the category of very appropriate with a percentage of 83%, while the quality of the education staff was in the category of less appropriate with a percentage of 46.86%. As for the results of the SWOT analysis, SDN Pamijahan has high strengths and opportunities for educators and educational staff, especially school principals, where almost all qualifications have been met. Meanwhile, most of the weaknesses and threats are to the education staff, such as the absence of special administrative staff, laboratory assistants, and librarians. After the SWOT analysis was carried out, strategies and action plans were also designed as a follow-up to improve the quality of educators and education personnel at SDN Pamijahan.